Anti‐Jka that are detected by solid‐phase red blood cell adherence but missed by gel testing can cause hemolytic transfusion reactions. Issue 12 (5th September 2016) - Kay, Brian; Poisson, Jessica L.; Tuma, Christopher W.; Shulman, Ira A.
Abstract : BACKGROUND: Kidd blood group antibodies are notorious for transient detection and hemolytic transfusion reactions. This report compares the rate of detection of anti‐Jk a when using gel column agglutination versus solid‐phase red blood cell adherence (SPRCA) testing and documents the occurrence of hemolytic transfusion reactions in 17 recently transfused patients who developed anti‐Jk a that were detectable by SPRCA but were undetectable by gel. STUDY DESIGN AND METHODS: Before April 20, 2011, the laboratory used gel column agglutination as the primary method for antibody screening and identification. From April 20, 2011, to August 12, 2013, SPRCA was adopted as the primary method for antibody screen with gel remaining the primary method for identification. SPRCA identification was also performed if sufficient sample was available. Medical records were reviewed for evidence of hemolytic reaction in patients whose anti‐Jk a was negative or inconclusive by gel, but clearly identifiable by SPRCA at the time the anti‐Jk a was first identified. RESULTS: A total of 105 patients were discovered with anti‐Jk a from 88, 478 SPRCA screens performed. In 32 patients, anti‐Jk a was initially discovered by SPRCA testing and concurrent gel testing was completely negative (n = 26) or inconclusive (n = 6). Seventeen of the 32 patients were recently transfused and of these six met criteria for delayed hemolytic transfusion reaction (DHTR), three had possible DHTRs, and eight had delayed serologic reactions; 13 of the transfused patients received Jk(a–) RBCs to avoid potential hemolysis. CONCLUSION: SPRCA testing significantly increased the discovery of clinically significant anti‐Jk a and facilitated the earlier use of Jk(a–) RBCs to avoid hemolytic transfusion reactions.